RC-IGBT snapback suppression using silicon germanium collector regions - Yoon, Tae Young; Park, Dong Gyu; Kim, Seong Yun; Kim, Garam; Kim, Sangwan; Kim, Jang Hyun (Journal of Power Electronics, 2024)
In this study, two new structures are proposed for reverse-conducting insulated gate bipolar transistors (RC-IGBT) that effectively prevent snapback by relocating the N-collectors and utilizing silicon–germanium in the collector region of each device. The forward mode of the proposed structures shows IC− VC characteristics without snapback, since the position of the N-collector is changed to prevent electron extraction. In the reverse mode, the silicon–germanium induces currents through tunneling and impacts the ionization mechanisms. Importantly, the proposed structures generate a stable current value even if there are errors in the length of the N-collector during ion implantation, which enhances the reliability of the device. In addition, the proposed structures exhibit similar values for the breakdown voltage at around 700 V and the turn-on and turn-off losses when compared to the conventional RC-IGBT. Thus, this paper improves the reliability of RC-IGBTs by mitigating the snapback effect while maintaining their unique electrical properties.
Keywords: 'current; Electron extraction; Forward mode; Insulatedgate bipolar transistor (IGBTs); Reverse conducting; Reverse mode; Reverse-conducting insulated gate bipolar transistor; Silicon germaniums (SiGe); Snapback effect; Tunneling; Impact ionization; RC-IGBT; Silicon germanium; Snapback effect; Tunneling